2014
DOI: 10.14411/eje.2014.011
|View full text |Cite
|
Sign up to set email alerts
|

Endosymbiotic microorganisms of aphids (Hemiptera: Sternorrhyncha: Aphidoidea): Ultrastructure, distribution and transovarial transmission

Abstract: Abstract. The ultrastructure, distribution and transovarial transmission of endosymbiotic bacteria in representatives of six aphid families: Eriosomatidae (Pemphigus spyrothecae, Prociphilus fraxini), Anoeciidae [Anoecia (Anoecia) corni], Drepanosiphidae [Mindarus abietinus, Sipha (Rungsia) maydis, Clethrobius comes, Myzocallis (Lineomyzocallis) walshii], Thelaxidae (Thelaxes dryophila), Aphididae (Delphiniobium junackianum, Aphis viburni, Cavariella theobaldi, Macrosiphoniella tanacetaria) and Lachnidae (Schi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
43
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(50 citation statements)
references
References 99 publications
(118 reference statements)
7
43
0
Order By: Relevance
“…One crucial question within the field is how do these associations evolve. This fact, in combination with previously published microscopic (Buchner, 1953;Fukatsu and Ishikawa, 1998;Lamelas et al, 2008;Pyka-Fo sciak and Szklarzewicz, 2008;Michalik et al, 2014) . In the Lachninae subfamily of aphids, it has previously been proposed that an ancient loss of the riboflavin biosynthetic capability by Buchnera promoted the settlement of a co-obligate secondary endosymbiont (putatively S. symbiotica) in the LLCA (Manzano-Mar ın and Latorre, 2014; Manzano-Mar ın et al, 2016).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…One crucial question within the field is how do these associations evolve. This fact, in combination with previously published microscopic (Buchner, 1953;Fukatsu and Ishikawa, 1998;Lamelas et al, 2008;Pyka-Fo sciak and Szklarzewicz, 2008;Michalik et al, 2014) . In the Lachninae subfamily of aphids, it has previously been proposed that an ancient loss of the riboflavin biosynthetic capability by Buchnera promoted the settlement of a co-obligate secondary endosymbiont (putatively S. symbiotica) in the LLCA (Manzano-Mar ın and Latorre, 2014; Manzano-Mar ın et al, 2016).…”
Section: Discussionsupporting
confidence: 83%
“…This has been evidenced through phylogenetic reconstructions using Buchnera DNA or amino acid sequences, which parallel their aphid hosts' evolutionary relationships (Munson et al, 1991;Jousselin et al, 2009;Liu et al, 2013). These secondary symbionts have a very different tissue tropism than Buchnera, as they can be present in separate bacteriocytes (called secondary bacteriocytes), coinfecting the primary endosymbiont's bacteriocytes, located in sheath cells (at the periphery of the bacteriome and found closely associated to bacteriocytes) and/or free in the haemocoel (Fukatsu et al, 2000;Sandstr€ om et al, 2001;Moran et al, 2005;Sakurai et al, 2005;Michalik et al, 2014). Contrary to obligate symbionts, facultative ones are not required for the correct development, reproduction and survival of their host.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier histological analyses (MÜLLER 1962, BUCHNER 1965, as well as more recent ultrastructural ones, have shown that hemipterans developed various means of transmitting symbionts from one generation to the next (CHENG & HOU 2001, SZKLARZEWICZ & MOSKAL 2001, SZKLARZEWICZ et al 2006, SACCHI et al 2008, MICHALIK et al 2009, 2014a, 2014b, KUECHLER et al 2010, MATSUURA et al 2012, SWIATONIOWSKA et al 2013. Symbionts may infect larval ovaries containing undifferentiated germ cells or ovaries of adult females containing vitellogenic or choriogenic oocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Both the histological (Müller, 1962;Buchner, 1965) and ultrastructural observations (Cheung and Purcell, 1999;Szklarzewicz and Moskal, 2001;Szklarzewicz et al, 2006Szklarzewicz et al, , 2013Sacchi et al, 2008;Michalik et al, 2009Michalik et al, , 2013Michalik et al, , 2014Kuechler et al, 2010Kuechler et al, , 2012Matsuura et al, 2012;Swiatoniowska et al, 2013) have revealed that hemipterans have developed different modes of transovarial transmission of bacteriocytes endosymbionts. These microorganisms may infest larval ovaries containing undifferentiated germ cells (¼cystocytes) or ovaries of adult females (in most hemipterans).…”
Section: Discussionmentioning
confidence: 99%